Electrocatalytic Reduction of CO2 to Acetic Acid by a Molecular Manganese Corrole Complex. Issue 26 (8th May 2020) - De, Ratnadip; Gonglach, Sabrina; Paul, Shounik; Haas, Michael; Sreejith, S. S.; Gerschel, Philipp; Apfel, Ulf‐Peter; Vuong, Thanh Huyen; Rabeah, Jabor; Roy, Soumyajit; Schöfberger, Wolfgang
Abstract: The controlled electrochemical reduction of carbon dioxide to value added chemicals is an important strategy in terms of renewable energy technologies. Therefore, the development of efficient and stable catalysts in an aqueous environment is of great importance. In this context, we focused on synthesizing and studying a molecular Mn III ‐corrole complex, which is modified on the three meso ‐positions with polyethylene glycol moieties for direct and selective production of acetic acid from CO2 . Electrochemical reduction of Mn III leads to an electroactive Mn II species, which binds CO2 and stabilizes the reduced intermediates. This catalyst allows to electrochemically reduce CO2 to acetic acid in a moderate acidic aqueous medium (pH 6) with a selectivity of 63 % and a turn over frequency (TOF) of 8.25 h −1, when immobilized on a carbon paper (CP) electrode. In terms of high selectivity towards acetate, we propose the formation and reduction of an oxalate type intermediate, stabilized at the Mn III ‐corrole center. Abstract : Electrochemical reduction of CO2 to acetic acid is achieved with a molecular Mn III ‐corrole complex. Electroreduction of Mn III leads to the electroactive Mn II species, which binds CO2 and stabilizes the reduced intermediates to allow the reduction of CO2 to acetic acid in a moderately acidic aqueous medium (pH 6) with a selectivity of 63 % and a turnover frequency of 8.25 h −1, when immobilized on a carbon paper (CP) electrode.